An insight into the bactericidal and phytochemical properties of leaf extract of Vernonia squarrosa and understanding antibacterial activity by molecular docking - Adwaita Das; Sunanda Burman; Chandan Das; Moitri Bhadra; Sumita Mondal; Pratiti Rakshit; Goutam Chandra; Abhijit Bandhyopadhyay (Elsevier, 2024)
Introduction: Numerous plants in the Vernonia genus are used in Traditional Chinese Medicine (TCM) to treat a wide range of illnesses, such as pityriasis rubra pilaris, infections, wounds, dermatitis, mastitis, diarrhoea, and colds. These genera also have antibacterial, antipyretic, and anti-inflammatory properties. The current work sought to investigate the bactericidal and phytochemical characteristics of Vernonia squarrosa leaf extract and comprehend antibacterial action using molecular docking. Methods: An in vitro study was carried out to investigate the antibacterial capabilities of V. squarrosa. HRLCMS analysis was conducted to determine the phytoconstituents of the chloroform extract (LC). For molecular docking validation, PyRx, an Open Babel integrated Auto Dock programme, was used. Results: Present investigation reveals strong antibacterial activity against two tested gram-positive and gram-negative bacterial strains compared to other solvent extracts, LC at a higher concentration demonstrated a better response. Against Bacillus subtilis (20.05±0.88 mm) and Escherichia coli (20 ± 0.00 mm), the active components of the extracts formed the largest inhibitory zone followed by Pseudomonas aeruginosa (19.50±0.50 mm) and Staphylococcus aureus (14.33 ± 0.33 mm). The LC extract had lower minimum inhibitory concentrations (MIC) and stronger bactericidal activity than the other extracts. Discussion: V. squarrosa's LC showed higher levels of antibacterial activity against the tested bacterial strains than other solvent extracts, most likely as a result of the presence of 31 chemical components, including flavonoids, glycosides, alkaloids, phenolics, and triterpenoids. Developing unique TCM formulations assume significance in global healthcare scenarios to combat bacterial infections and in this context, the current paper underlines the importance of the potent antimicrobial properties of chloroform extract of V. squarrosa. This study revealed that chloroform extract of V. squarrosa has a great deal of antibacterial activity. Conclusion: According to the study, V. squarrosa leaf chloroform extract possesses antibacterial properties because of its active phytocompounds. Its wide range of bioactive components makes it a prime choice for developing novel formulations to neutralize threats of newly emerging strains of harmful bacteria. The aforementioned discoveries may deepen our comprehension of phenomenal wisdom and deep science associated with the legendary TCM.